Protective immunity and specificity of antibody response elicited in cattle by irradiated Trypanosoma brucei - Morrison, W. Ivan; Black, Samuel J.; Paris, J.; Hinson, C.A.; Wells, P.W. (Wiley, 1982)
The level and specificity of antibody responses elicited in cattle by irradiated non‐infective Trypanosoma brucei were examined and related to the development of protective immunity. These responses were compared with those induced by infection and by inoculation with purified variable surface glycoprotein (VSG) in adjuvant. It was found that 107 or more irradiated trypanosomes inoculated intravenously into cattle conferred complete protection against challenge with 103 homologous trypanosomes 14 days later. Animals immunized with 106 organisms showed partial protection. Of the assays used for detection of antibody, neutralization of infectivity was slightly more sensitive than either the Farr assay or the immunofluorescence test which were both more sensitive than solid‐phase radioimmunoassay (RIA). Detection of specific antibody correlated with immunity, in that all animals inoculated intravenously with 106 or more trypanosomes developed neutralizing activity in their sera. The antibody responses after intravenous inoculation were consistently superior to those induced by the subcutaneous route. By carrying out blocking assays, most of the antibody elicited by irradiated trypanosomes was found to be specific for antigenic determinants on the VSG exposed on the surface of live trypanosomes. A similar specificity was found for the antibody induced during infection with T. brucei. Conversely, a large component of the antibody induced by purified VSG in adjuvant appeared to be directed against determinants on the VSG which are not exposed on live trypanosomes and are probably not involved in protective immunity.